2010
DOI: 10.1111/j.1651-2227.2010.01885.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of infants’ position on serum bilirubin level during conventional phototherapy

Abstract: The decrease in TSB was not significantly associated with positioning of the infant during conventional phototherapy. Alternating exposure is widely practiced in Scandinavia but is unnecessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 9 publications
3
40
0
Order By: Relevance
“…This agrees with the findings of Donneborg et al (17), who showed that changing the position of infants during phototherapy, as is common practice, does not increase the effect of phototherapy. They inferred that the effect of phototherapy is in the capillary circulation near the skin surface.…”
Section: Discussionsupporting
confidence: 83%
“…This agrees with the findings of Donneborg et al (17), who showed that changing the position of infants during phototherapy, as is common practice, does not increase the effect of phototherapy. They inferred that the effect of phototherapy is in the capillary circulation near the skin surface.…”
Section: Discussionsupporting
confidence: 83%
“…With reference to a 24-h decrease of TSB in a previous study (22), the sample size was calculated to demonstrate a 6% difference in the decrease of TSB between the groups after 24 h of phototherapy, a difference judged as clinically relevant. Determining a significance level of 0.05 and a power of 0.8, the required sample size should be at least 36 infants in each group.…”
Section: Subjectsmentioning
confidence: 99%
“…13 Changing position has been known to maximize the area exposed to light resulting the reduction of phototherapy duration. 7 Our findings the decreasing amount of serum bilirubin levels before and after 24 hours of phototherapy showed a statistically no significant result between the alternating positioned group and the supine only positioned group (P=0.751). A randomized study in Israel on 30 aterm infants reported that total serum bilirubin level decreased significantly in infants with supine position.…”
Section: Discussionmentioning
confidence: 58%
“…7 The assessment of baseline characteristics in both groups from this study includes gender, birth weight, gestational age, body temperature, feeding, hemoglobin, hematocrit, leucocytes, platelets, reticulocyte, CRP, Coomb tests, and light irradiance. The average age of neonatal phototherapy began at age 4 to 5 days, this is related to an increase in bilirubin levels peak at age 3 to 5 days.…”
Section: Discussionmentioning
confidence: 99%